An Investigation on The Local Flora of WANAPARTHY For Its Therapeutic Properties - K. Sunitha Bai; Gulab Singh (Journal of Biomedical and Pharmaceutical Research, 2023)
There are 355 plant species total in the Government Degree and PG College campus in Wanaparthy; 15 of them are unique to the area. There were also a significant variety of medicinal plants, wild relatives, fodder plants, and edible plants found in the area. The findings showed that the college campus has an abundance of plant species, which is great for the academic pursuits of the student body. Keyword: Conservation, Endangered, Economic Importance, Related Species, Wild.